5510 SAYILI SOSYAL SİGORTALAR VE GENEL SAĞLIK SİGORTASI KANUNUNUN EK 9 UNCU MADDESİ KAPSAMINDA EV HİZMETLERİNDE ÇALIŞANLARIN SİGORTALILIĞI - (:unkn) unknown (My University, 2015)
Ev hizmetlerinde çalış anların sigortalılığına iliş kin en köklü değiş iklik 11.09.2014 tarihli resmi gazetede yayımlanarak yürürlüğe giren 6552 Sayılı Torba Kanun ile 5510 Sayılı Sosyal Sigortalar ve Genel Sağlık Sigortası Kanununa eklenen Ev hizmetlerinde çalı ş anların si- gortalılığı baş lıklı ek m. 9 hükmü ile yapılmış tır. Ayrıca, ek m. 9/f 5 hükmünün verdiği yetki uyarınca, söz konusu madde hükmünü ve uygulama prensiplerini açıklığa kavuş turmak amacıyla Ev Hizmetlerinde 5510 Sayılı Kanunun Ek 9 uncu Maddesi Kapsamında Sigortalı Çalış tırılması Hakkında Tebliğ Kurum tarafından 01.04.2015 tarihinde Resmi Gazetede yayımlanarak yürürlüğe girmiş tir. Bu çalış mamızda, 5510 Sayılı Sosyal Sigortalar ve Genel Sağlık Sigortası Kanununa eklenen ek m. 9 hükmü, 6552 sayılı Torba Kanun ile değiş ikliğe uğrayan m. 6/I, c hükmü ve Kurum Tebliği kapsamında ev hizmetlerinde çalış anların sigortalılığına iliş kin yeni düzenlemeler inceleme konusu yapılacaktır.

The most major change regarding insurance of the household workers has been made by the additional article no. 9 with the subject of Insurance of household workers which has been added to Law No. 5510 regarding the Social Security and General Health Insurance Law by the Omnibus Law No. 6552 regarding the changes in the Labour Law, some other Laws and Legislative Decrees and Reconstruction of Some Debts. Also as per the authorization provided by the additional article no. 9/5, in order to clarify the mentioned article and the application principles, Declaration regarding the employment of workers in household works within the scope of the additional article no. 9 of Law No. 5510 has come into effect published by the Social Security Institution being in the Official Journal dated 01.04.2015. In this study, we will review the additional article no. 9 which has been added to Law No. 5510 regarding the Social Security and General Health Insurance Law, the article no. 6/I, c which has been changed by the Omnibus Law No. 6552 and the regulations regarding the insurance of the household workers within the context of Social Security Institution declaration.
(THE INSURANCE OF HOUSEHOLD WORKERS WITHIN THE SCOPE OF THE ADDITIONAL ARTICLE NO. 9 OF THE SOCIAL SECURITY AND GENERAL HEALTH INSURANCE LAW NO. 5510)
Keywords: Hukuk